THE IMPACT OF TEACHER’S PHYSICAL PRESENCE IN CLASS: BODY LANGUAGE AND VOICE - Ubaydullaeva Muxlisa (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article explores the significance of a teacher’s physical presence in the classroom, focusing on body language and voice as essential tools for effective teaching. It examines how nonverbal communication influences student engagement, classroom management, and learning outcomes. The study highlights research-based strategies for teachers to enhance their presence through purposeful gestures, posture, eye contact, and vocal techniques. Practical implications for classroom teaching are also discussed.